Analisis Penggunaan Dana Pemerintah Terhadap Pemekaran Nagari Di Kabupaten Pasaman Barat - Tia Yosiska; Kusmilawaty Kusmilawaty (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this study was to find out the process of using the budget funds carried out by Kenagarian in the expansion of Nagari in every sub-district in West Pasaman Regency. The approach used in this study is descriptive qualitative, that is, after the data has been collected, a qualitative analysis is carried out and describes one data with other data in such a way as to obtain a complete general picture of the problem under study. Then the data collection method uses observation, interviews, and documentation. The results of this study indicate that the use of government funds in each Nagari is considered not good. The system for using it is by giving funds from one party to another so that there is a discrepancy between the amount of funds budgeted for and the use of funds in each Nagari. This is because responsible parties such as the head of the Wali Nagari do not go directly to the field, but only utilize staff or give this responsibility to their subordinate staff.Therefore, it can be suggested that there be further training and coaching regarding the implementation of the Government Fund budget for Nagari apparatus, which of course is organized training on management and administration of ADD management from professionals in their fields, the Nagari Government must involve more of the entire Village community in Development activities.The Nagari government must be more disciplined in carrying out its duties and responsibilities, especially in preparing accountability reports.